Performance of a 35.2 kWp Roof Top Grid-Connected Solar Photovoltaic Power Plant in Tribal Region of Gujarat: RESEARCH PAPER - T. V. Chavda; Alok Singh; S. H. Sengar (Annals of Arid Zone, 2025)
In India, rooftops and underutilized lands are increasingly being harnessed for solar photovoltaic (PV) installations to generate electricity. A prominent example is the 35.2 kWp grid-connected solar PV power plant installed on the rooftop of the College of Agricultural Engineering and Technology at Navsari Agricultural University (NAU), Dediapada (located at 21.66°N and 73.59°E), in May 2018. Situated on the top floor at approximately 10 meters above ground with a 20° tilt, this project aimed to evaluate the performance and efficiency of the solar PV system in Gujarat’s tribal region. This study assesses the system’s performance from January 2019 to December 2022, during which all generated electricity was fed into the state grid. Key performance parameters analyzed include final yield, reference yield, array yield, system losses, array capture losses, cell temperature losses, PV module efficiency, system efficiency, inverter efficiency, performance ratio, and capacity factor. Over the monitoring period, the system produced a total of 202.3 MWh of electricity, with the PV modules achieving an efficiency of 12%, the inverter operating at 95% efficiency, and a performance ratio of 0.7.